Short Communication: DNA extraction from stored wood of Falcataria moluccana suitable for barcoding analysis - HASYYATI SHABRINA; ULFAH J SIREGAR; DEDEN D MATRA; KOICHI KAMIYA; ISKANDAR Z SIREGAR (Society for Indonesian Biodiversity, 2019)
Abstract. Shabrina H, Siregar UJ, Matra DD, Kamiya D, Siregar IZ. 2019. Short Communication: DNA extraction from stored wood of Falcataria moluccana suitable for barcoding analysis. Biodiversitas 20: 1748-1752. Sengon or Falcataria moluccana (Miq.) Barneby & J.W.Grimes is the main crop in community tree plantations in Java, Indonesia, favored because of its fast-growing property and the promising economic return. The wood itself is mostly used for light construction, furniture, plywood, packing materials, and recently as feedstock for bioenergy. Sometimes the wood is used as DNA source for example in the wood identification analysis. However, extracting DNA from woods is considered difficult due particularly to very small quantities of DNA. The objective of this research was to optimize and modify the common CTAB protocols to extract DNA from Sengon wood without liquid nitrogen which sometimes unavailable in some laboratories. The extracted DNA was quantified with nanophotometer and gel visualization and amplified with primer coding psbA-trnH intergenic spacer for testing. The highest concentration of DNA extracted was from 100 mg of wood stored for 24 hours in -30 °C (257.80 ng/µL or 14.18 µg in total) and even the lowest concentration produced by this method able to produce sufficient amount of PCR product for sequencing. Compared with results from 200 mg samples and longer freezing time (72 hours) and extraction using liquid nitrogen, this method considered gave the best results.